All Days 2014
DOI: 10.2523/iptc-17440-ms
|View full text |Cite
|
Sign up to set email alerts
|

New Sour Gas Corrosion Inhibitor Compatible with Kinetic Hydrate Inhibitor

Abstract: The presence of hydrogen sulfide in high pressure gas systems causes several complications. Sour gas corrosion is a major concern in the oil and gas industry due to the presence of localized corrosion. At high pressures and low temperatures hydrates can occur. Sour gas decreases the pressure and increases the temperature at which hydrate formation occurs. Operators have used both corrosion inhibitors and kinetic hydrate inhibitors to decrease the capital requirements of developing sour high pressure gas system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…More surprisingly, addition of NaPh 4 B almost totally killed the PVCap KHI effect, raising the average T o value to 15.2 °C. This effect is reminiscent of some oilfield corrosion inhibitors, which are also known to be antagonistic with certain KHI polymers. We conclude that the tetraphenyl salts, particularly the borate salt, are probably interacting with the PVCap polymer rendering it less available for kinetic hydrate inhibition. On the contrary, the promoting effect of NaPh 4 B might lend itself to applications where rapid hydrate formation is required, for example in storage and transport of natural gas as gas hydrate.…”
Section: Background Results and Discussionmentioning
confidence: 85%
“…More surprisingly, addition of NaPh 4 B almost totally killed the PVCap KHI effect, raising the average T o value to 15.2 °C. This effect is reminiscent of some oilfield corrosion inhibitors, which are also known to be antagonistic with certain KHI polymers. We conclude that the tetraphenyl salts, particularly the borate salt, are probably interacting with the PVCap polymer rendering it less available for kinetic hydrate inhibition. On the contrary, the promoting effect of NaPh 4 B might lend itself to applications where rapid hydrate formation is required, for example in storage and transport of natural gas as gas hydrate.…”
Section: Background Results and Discussionmentioning
confidence: 85%
“…The obtained results in this work suggested that the performance of KHIs might be deteriorated at high pH conditions, suggesting the supplementary action to implement both the kinetic inhibition for hydrates and pH control for corrosion. Moreover, recent studies have reported compatible issues between KHIs and corrosion inhibitors (CIs). The interaction between the functional groups of KHIs and CIs must be investigated thoroughly under various pH conditions. Yu et al suggested that the change in the pH caused changes in the polymer conformation, which potentially led to coagulation and could result in a reduction in the hydrate inhibition performance.…”
Section: Resultsmentioning
confidence: 99%
“…Corrosion inhibitors (CIs) are used to prevent pipeline corrosion, since this is the most effective method. , Generally, operators inject KHIs and CIs to flow lines at the same time. Thus, it can cause incompatibility problems between them due to their different nature (chemical structure). It has also been reported that corrosion inhibitors can promote hydrate formation at different rates depending on their structure and functional group . A possible solution to overcome this problem is to design a single molecule that can inhibit both corrosion and hydrate formation, simultaneously. ,, Another option is to add a proper synergist to KHI formulation for preventing corrosion and improving hydrate inhibition performance.…”
Section: Introductionmentioning
confidence: 99%